2010
DOI: 10.2106/jbjs.i.01176
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Versus Functional Treatment for Acute Ruptures of the Lateral Ligament Complex of the Ankle in Young Men

Abstract: These findings indicate that, in terms of recovery of the preinjury activity level, the long-term results of surgical treatment of acute lateral ligament rupture of the ankle correspond with those of functional treatment. Although surgery appeared to decrease the prevalence of reinjury of the lateral ligaments, there may be an increased risk for the subsequent development of osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 13 publications
1
45
0
5
Order By: Relevance
“…Since this review was conducted, at least two more randomized controlled trials have been published comparing conservative and surgical management for acute lateral ligament complex injuries [8,11]. Both of these trials failed to demonstrate significant differences between surgery and conservative management in their primary outcomes, further corroborating the findings of this Cochrane review.…”
Section: Take-home Messagessupporting
confidence: 67%
See 1 more Smart Citation
“…Since this review was conducted, at least two more randomized controlled trials have been published comparing conservative and surgical management for acute lateral ligament complex injuries [8,11]. Both of these trials failed to demonstrate significant differences between surgery and conservative management in their primary outcomes, further corroborating the findings of this Cochrane review.…”
Section: Take-home Messagessupporting
confidence: 67%
“…A single trial published by Prins [10] in 1978 demonstrated several benefits of surgical management -results that differed substantially from other published trials, including several more-recent and better-designed efforts [8,[11][12][13] -and greatly influenced the pooled estimate for many outcomes. The pronounced and, occasionally differing, direction of Prins' results may be attributable to the trial being only quasi-randomized, resulting in no concealment of treatment allocation or blinding.…”
Section: Upon Closer Inspectionmentioning
confidence: 99%
“…They concluded that surgical repair and functional treatment of these injuries resulted in equivalent results with respect to recovery to preinjury activity level. Although surgery did appear to decrease the incidence of lateral ligament reinjury in their study population, the found that osteoarthritis was observed significantly more frequently in the surgical group [71] .…”
Section: Level Of Competitionmentioning
confidence: 77%
“…Conversely, Tiling et al [70] performed a thorough review of 24 trials comparing surgical and functional management of ankle sprains and concluded that no significant difference was found between the two treatment strategies. More recently, in 2010, Pihlajamäki et al [71] reported the results of their prospective randomized trial, in an active Finnish patient population. These authors compared functional management to suture repair of ruptured ligaments within 1 wk of injury for acute grade Ⅲ lateral ankle ligaments.…”
Section: Level Of Competitionmentioning
confidence: 99%
“…The overall conclusion was that there was insufficient evidence available from randomized controlled trials to recommend surgical or conservative treatment for those with acute lateral ligament sprains. 140 A recent study 200 compared surgery to functional treatment for acute grade III (severe) lateral ligament injuries. Physically active males (mean age, 20.4 years) with acute grade III injuries were randomly allocated to surgical (n = 25) or functional (n = 26) treatment.…”
Section: Clinical Coursementioning
confidence: 99%